TINGKAT KEPUASAN NASABAH TERHADAP FASILITAS LAYANAN DEBIT CARD DI PT BANK CENTRAL ASIA TBK CABANG CIRENDEU - Rosalina Ayudia (Institut Teknologi dan Bisnis Swadharma, 2020)
Bank Central Asia is the largest private bank in Indonesia established in 1957, through a variety of quality and targeted products and services, BCA financial solutions support financial planning and the development of business customers. Supported by the strength of the network between branches, the breadth of the ATM network, and other electronic banking networks, anyone can enjoy the convenience and convenience of transactions offered by BCA. The author pays attention to the customers of each bank in Indonesia in improving the capacity of the Debit Card services provided to their respective customers. The author is like in place of interbank rivals to improve the Debit Card service. Based on the results of respondent data, customers who become many debit card users are female, the average age of users is 20 to 40 years, where this age is included in the productive period, and customers who work as entrepreneurs are customers using debit cards. the most dominant, and the most dominant type of debit card used by customers is platinum where this type is the most commonly used type of debit card